KAJIAN ASPEK FINANSIAL INDUSTRI MINUMAN BUBUK KUNYIT ASAM - Satriawan, I Ketut; Mulyani, Sri (Agrotekno; Vol. 13, No. 1 Februari 2007)
Beverage  of “kunyit-asam”  was being familiar  in  the society  as  a  traditional  herbs,  fresh  beverage,  and  potential antioxidant. However,  it’s industry  not  yet much done in home industry scale.This  research aimed to  evaluate  investment  value which needed  and  financial  feasibility  of “kunyit-asam” powderindustry  in home  industry  scale.  The  analysis  which  used in financial  feasibility  i.e. :  Net Present Value (NPV),  InternalRate of Return (IRR),  Pay Back Period (PBP),  Break EvenPoint (BEP), Net Benefit-Cost Ratio (Net  B/C), and sensitivityanalysis.Investment value which needed for planning  of “kunyit-asam”  powder industry  in  home  industry  scale  is  Rp. 52.364.065.  The  analysis  of  financial  feasibility  of  “kunyit-asam”  powder industry in home industry scale is feasible based on some value of investment criteria.
Keywords: “kunyit-asam”powder, financial analysis